STRATEGI PENDIDIKAN KEMANDIRIAN ANAK (Studi Di Madrasah Ibtidaiyah Muhammadiyah Ponorogo) - Katni . (Universitas Muhammadiyah Ponorogo, 2015)
This study aims to describe the independence education materials, the independence education strategy, and the independence education results in MI Muhammadiyah Ponorogo. This qualitative research used observation, questionaire, and documentation in collecting the data which was analyzed with the qualitative descriptive analysis. This study found that the independence education materials given to the first up to the third grade students of MI Muhammadiyah Ponorogo was focused on fostering on selfcare. While the materials for the fourth up to sixth grade students of MI Muhammadiyah Ponorogo had been increasingly complex, in addition to selfcare purpose, it was also about respecting friends and families. Furthermore, independence education in MI Muhammadiyah Ponorogo done through two tracks. On children lane, it was developed through example to take care themselves, through advices, consel, and commands as well as ASLAMA method (Asrama Semalam di Madrasah or overnight boarding). While on the parents lane was done through guidance in order to work together in developing their children attitude and coaching them. This independence education, was further evaluated every Monday.